Responsible leadership and ethical decision-making - Savur, Sunil; Sandhu, Sukhbir (Research in ethical issues in organizations ;, 2017)
This book is comprised of international author perspectives from the 2016 Australian Association for Professional and Applied Ethics (AAPAE) conference, hosted by the University of South Australia in Adelaide. The volume brings to life a number of the conference themes including corporate social responsibility, culture, academic integrity, vulnerability, health, military ethics, education, leadership, sustainability and philosophy and addresses concerns of many leading applied ethicists.